2006
DOI: 10.1111/j.1365-2486.2006.01197.x
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal, seasonal and annual variation in net ecosystem CO2 exchange of an alpine shrubland on Qinghai‐Tibetan plateau

Abstract: Thus far, grassland ecosystem research has mainly been focused on low-lying grassland areas, whereas research on high-altitude grassland areas, especially on the carbon budget of remote areas like the Qinghai-Tibetan plateau is insufficient. To address this issue, flux of CO 2 were measured over an alpine shrubland ecosystem (37136 0 N, 101118 0 E; 3250 m above sea level [a. s. l.]) on the Qinghai-Tibetan Plateau, China, for 2 years (2003 and 2004) with the eddy covariance method. The vegetation is dominated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
109
6
12

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 183 publications
(145 citation statements)
references
References 37 publications
18
109
6
12
Order By: Relevance
“…For the two sites located in shrublands (USSO4 and USKS2) water limitation might have played a role, since the overestimation was much larger for the site located in a water-limited area (USSO4) compared to non-water limited areas. This overestimation by GPPm could be attributed to the fact that the DAO meteorology used by the MOD17 algorithm underestimates local VPD in many waterlimited sites during the summer, and therefore photosynthesis is not sufficiently constrained when calculating GPPm for dry periods in North America [13,42]. This result agrees with [13], who found a similar overestimation of 67% for an open shrubland site in a dry area.…”
Section: Suitability Of the Modis Gpp Product To Estimate Annual Gpp supporting
confidence: 81%
“…For the two sites located in shrublands (USSO4 and USKS2) water limitation might have played a role, since the overestimation was much larger for the site located in a water-limited area (USSO4) compared to non-water limited areas. This overestimation by GPPm could be attributed to the fact that the DAO meteorology used by the MOD17 algorithm underestimates local VPD in many waterlimited sites during the summer, and therefore photosynthesis is not sufficiently constrained when calculating GPPm for dry periods in North America [13,42]. This result agrees with [13], who found a similar overestimation of 67% for an open shrubland site in a dry area.…”
Section: Suitability Of the Modis Gpp Product To Estimate Annual Gpp supporting
confidence: 81%
“…Some studies have revealed the stability of soil processes underground in a drought experiment, semiarid soil microbiological parameters including microbial biomass and extracellular enzyme activities showing a sufficient resistance and a rapid recovery after soil rewetting (Hueso et al 2011). So far, most studies that simulated drought events have been done in semiarid and Mediterranean region (De Boeck et al 2011;Godfree et al 2011;Jentsch et al 2011;Jimenez et al 2011;Penuelas et al 2007;Rich et al 2008), but not on the Tibetan Plateau , where the unique geography yields relatively high vegetation growth with concentrated rainfall during the growing season, but overall very slow soil organic matter decomposition rates during dry cold winters (Kato et al 2006;Zhao et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Goulden et al, 1996;Suyker et al, 2005;Moureaux et al, 2006;Zhao et al, 2006); and (ii) the "correction approach", based on a direct estimation of all the CO 2 balance terms, including the advection terms (e.g. Aubinet et al, 2003Aubinet et al, , 2005Feigenwinter et al, 2004;Staebler and Fitzjarrald, 2004;Marcolla et al, 2005;Sun et al, 2007;Yi et al, 2008;Montagnani et al, 2009).…”
Section: Introductionmentioning
confidence: 99%